Sociopragmatic parameters of politeness strategies among the Sasak in the post elopement rituals - Lalu Nurul Yaqin; Thilagavathi Shanmuganathan; Wulan Fauzanna; Mohzana Mohzana; Aswadi Jaya (Universitas Syiah Kuala, 2022)
Arranged marriages in Asia involve the consent and approval of family members. However, marriages that condone elopement are shared among the Sasak people in Lombok. The elopement entails taking away the bride from her home without knowing her parents, close relatives, or other family members. As such, events that occur after discovering the elopement are the focus of this study. Post-elopement rituals are held to assuage both sides of the families, where the Pembayun (or adat leaders) are nominated to represent the families. The Pembayun were found to be bound by sociopragmatics in their use of politeness strategies. The analysis of sociopragmatics is based on the politeness theories of Brown and Levinson (1987). A qualitative approach that involved interviews and video recordings were used to collect data from participants and non-participant observation. The study revealed that sociopragmatics play a significant role in Pembayun’s choice of politeness strategies such as social distance, power distribution, rank, situational, and cultural parameters. These factors determine the weightiness of the act and become the basis for politeness strategies in the deliverances of specific acts during the post-elopement rituals.